Approach to the legal and economic viability of the application of presumed consent as a public policy for the encouragement and promotion of organ and tissue donation in Peru - Paredes Aranda, Braylyn (2021)
In this article, the authors address the problem related to the low number of organ and tissue donations in Peru. A statistical review shows that the rate of organ and tissue donations is lower than in other countries in the region, while patient demand is higher than the number of organs available.  In this sense, from a constitutional and economic point of view, the authors develop the feasibility of implementing a public policy that postulates the substitution of informed consent for presumed tacit consent. To this end, first, they study the legal categories involved, their legal treatments, etc. Secondly, they analyze the current context of organ donation in the country, its operational shortcomings, lack of regulation, etc. Finally, they analyze the need and legal feasibility of formulating and implementing a change in the paradigm of the regulation of donations with the adoption of presumed consent as a central axis.